ANALYSIS OF THE EFFECTIVENESS OF LOCAL TAXES AND REGIONAL LEVIES ON THE ORIGINAL LOCAL GOVERNMENT REVENUE OF BEKASI - Hartanti Hartanti; Eka Dyah Setyaningsih; Ratiyah Ratiyah; Juwita Afriliyanah (Sean Institute, 2023)
Regional Governments finance routine expenses and other expenses budgeted in the APBD. One source of revenue in the APBD comes from Regional Original Income. Regional Taxes and Regional Levies are sources of Original Regional Income. This research aims to analyze the effectiveness and contribution of regional taxes and levies to the local revenue of the city of Bekasi for the 2018-2021 period. The analysis method uses qualitative descriptive methods, and data collection methods use observation, interviews, documentation/library study methods—data obtained from the Bekasi city regional government. The research results show that the effectiveness of regional tax revenues in 2018-2021 is, on average, practical and quite effective and has an outstanding contribution. This is because the policies and services implemented by the Bekasi city government effectively increase taxpayer compliance. Meanwhile, the effectiveness of regional levies in 2018-2021 is fluctuating, while the contribution is still felt insufficient, so an effective strategy is needed to increase the effectiveness and contribution of regional levies.